The Relationship between Communication Apprehension and Emotional Spiritual Quotient among Malaysian Students - Mustaffa, Che Su (EDUCARE, 2009)
ABSTRACT: Communication skills and emotional spiritual quotient are important for employees to achieve organizational goals and mission. In order to achieve the organizationâs objectives, the level of communication apprehension must be low and emotional spiritual quotient must be high. This research intends to find out the level of communication apprehension and emotional spiritual quotient of students, whether significant relationship exist between all the dimensions of communication apprehension and emotional spiritual quotient, and whether there exist any differences between the communication apprehension and emotional spiritual quotient based on demographic factors. A total of 340 respondents were selected using the stratified random sampling method. The results indicate that there exists a significant and positive relationship between communication apprehension and emotional spiritual quotient. There are no significant differences between communication apprehension and emotional spiritual quotient based on demographic factors. KEY WORDS: communication apprehension, emotional spiritual quotient, and Malaysian students.About the Author: Associate Professor Dr. Che Su Mustaffa is a Lecturer at the College of Arts and Sciences UUM (University of Utara Malaysia) in Sintok, Kedah, Malaysia. She can be reached at: chesu402@uum.edu.myHow to cite this article? Mustaffa, Che Su. (2009). âThe Relationship between Communication Apprehension and Emotional Spiritual Quotient among Malaysian Studentsâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.35-46. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 5, 2009); Revised (July 7, 2009); and Published (August 17, 2009).